2014
DOI: 10.1371/journal.pone.0112752
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to a Low Dose of Bisphenol A Impaired Systemic Cellular Immune Response and Predisposes Young Rats to Intestinal Parasitic Infection

Abstract: Perinatal exposure to the food contaminant bisphenol A (BPA) in rats induces long lasting adverse effects on intestinal immune homeostasis. This study was aimed at examining the immune response to dietary antigens and the clearance of parasites in young rats at the end of perinatal exposure to a low dose of BPA. Female rats were fed with BPA [5 µg/kg of body weight/day] or vehicle from gestational day 15 to pup weaning. Juvenile female offspring (day (D)25) were used to analyze immune cell populations, humoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 32 publications
5
51
1
2
Order By: Relevance
“…During the workshop, the participants considered that the two key studies performed by Ménard and colleagues needed further evaluation based on the identified immune effects at low BPA dosages (10, 11). At the workshop, these experimental studies were presented in detail by one of the authors Dr. Laurence Guzylack from INRA (Institut National de la Recherche Agronomique).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the workshop, the participants considered that the two key studies performed by Ménard and colleagues needed further evaluation based on the identified immune effects at low BPA dosages (10, 11). At the workshop, these experimental studies were presented in detail by one of the authors Dr. Laurence Guzylack from INRA (Institut National de la Recherche Agronomique).…”
Section: Introductionmentioning
confidence: 99%
“…Two manuscripts by Ménard et al (2014) (10, 11), that were published after the closure date of the literature search for the 2015 EFSA opinion, reported on immune effects of pre- and postnatal developmental low dose exposure to BPA on oral tolerance and immunization to OVA (10, 11) and on host resistance to infection with an intestinal parasite (11) in rats. Oral tolerance induction is a tightly regulated immunological process that takes place in the gut-associated lymphoid tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that the extent of cytokine suppression exposed to low and environmentally relevant BPA level, such as in our study, was not sufficient to significantly increase the risk of infection or nasopharyngeal bacterial colonization in infants. Third, the few available data that suggest certain pollutants to increase susceptibility to infection were mostly results from animal studies or exposure to environmental toxin other than BPA (such as dioxins, cigarette smoke, diesel exhaust, and other air pollutants) (30,31). To our knowledge, only two published studies implied BPA exposure to increase the risk of infectious diseases in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of human adverse effects of BPA exposure has recently been critically reviewed by the European Food Safety Authority (EFSA), concluding with a lowering of the recommended tolerable daily intake level of 50 mg/kg body weight per day to 5 mg/kg body weight per day (EFSA, 2015). Recent studies report immune effects at BPA levels at or below this exposure level, supporting the need for further insight into adverse immune effects of BPA (Menard et al, 2014a(Menard et al, , 2014b.…”
Section: Introductionmentioning
confidence: 94%